FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN MUSKULOSKELETAL PADA PENGRAJIN GERABAH DI DESA KAPAL MENGWI BALI - Hardiningrum, Luh Putu Larasati; Duana, I Made Kerta (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p06, 2025)
Musculoskeletal complaints are one of the most common occupational health problems in the workplace. Ergonomic problems in Indonesia can generally be identified in informal sector industries due to lack of attention to potential ergonomic hazards even though most production processes are still carried out traditionally. The pottery manufacturing industry includes informal industries whose workers are at risk of complaints of MSDs. Therefore, the purpose of this study is to determine the factors associated with complaints of MSDs in pottery craftsmen in Kapal Mengwi Village Bali. This type of research is analytical research with a cross-sectional research design. Data collection method through distributing questionnaires and filling out checklists of potential ergonomic hazards SNI 9011:2021. Data analysis using descriptive statistical tests, chi-square tests, and logistic regression tests. The results showed that most workers experienced high MSDs complaints (65.4%) with factors that were statistically related to MSDs complaints in pottery craftsmen in Kapal Mengwi Village Bali, namely ergonomic risk level (p = 0.024), age (p = 0.001), and length of service (p = 0.000). Workers are expected to pay attention to the risk of MSDs complaints, especially those who have a working period of ? 5 years by making preventive efforts related to the incidence of MSDs complaints, such as stretching or workplace stretching exercises to reduce acute effects and prevent chronic effects of MSDs due to work. Keywords: Musculoskeletal Disorders, Ergonomic, Pottery Craftsmen